Faktor yang Mempengaruhi Nilai Perusahaan Sektor Farmasi di Bursa Efek Indonesia - Omi Pramiana (MBR (Management and Business Review), 2020)
This study aims to analyze the effect of dividend policy, investment decisions, funding decisions, and financial performance on firm value. Using a quantitative research approach, data were collected using documentation techniques from company financial reports. The research sample was 45 pharmaceutical companies in the Indonesia Stock Exchange used the purposive sampling technique, while data analysis and hypothesis testing used Multiple Linear Regression. The results of the analysis show that dividend policy, investment decisions and financial performance have a positive effect on firm value, while funding decisions do not affect firm value.